A new straightforward uncalcined approach for morphology modulating to enhance the electrical capacity performance of Co-MOF. (1st September 2021) - Zhang, Haiyang; Sun, Ying; Zhang, Xueqin; Yang, Hong; Lin, Baoping
Abstract: Development of low-energy-consumption and low-cost process to prepare high-performance uncalcined MOF-based electrode materials is in line with the concept of green synthesis. We present here an uncalcined strategy of reorganizing the nano-sized MOF into a stable structure by anion intervention and doping with conductive substances to improve the conductivity. Three MOF electrode materials of Co-BTC nanoparticles (CBN), Co-BTC microspheres (CBM) and CNTs@Co-BTC microspheres (CCBM) have been prepared by a one-step approach of solvothermal. Results reveal that the introduction of phosphomolybdic acid (POM) can induce Co-BTC nanoparticles self-assemble into microspheres, which can provide CBM a superior specific capacitance compared to CBN. And doping with CNTs can further improve the electrochemical performance in term of the capacitance. Consequently, CCBM holds the highest specific capacitance as 553.3 F g −1 at 1 A g −1, and keeps an outstanding cyclic stability that retention of capacitance after 5000 cycles is around 90%.